2016
DOI: 10.1002/zaac.201500814
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth(III) Complexes Based on Bis(triazol) Ligands: Effect of Fluorine Substitution on the Structure and Catalysis for the Polymerization of Glycolide

Abstract: (Fbtx) were synthesized and characterized. Single-crystal X-ray diffraction revealed that 1 is a coordination polymer consisting of an anionic one-dimensional chain, whereas 2 shows a discrete ionic-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…31 Chen and co-workers studied the synthesis and catalytic activities of bis(triazol) derivatives of Bi 3+ complexes with fluorinated and nonfluorinated ligands in the bulk ROP of G and attained high-molar-mass (52 kg• mol −1 ) PGA homopolymers. 32 The melt ring-opening transesterification polymerization of PLAs has been studied using bismuth (III) subsalicylate (BiSS), an effective, relatively lowcost, and commercially available catalyst. 33 Low-molar-mass PGA samples display lower crystallinity, relatively poor thermal and mechanical behavior, and higher water permeability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Chen and co-workers studied the synthesis and catalytic activities of bis(triazol) derivatives of Bi 3+ complexes with fluorinated and nonfluorinated ligands in the bulk ROP of G and attained high-molar-mass (52 kg• mol −1 ) PGA homopolymers. 32 The melt ring-opening transesterification polymerization of PLAs has been studied using bismuth (III) subsalicylate (BiSS), an effective, relatively lowcost, and commercially available catalyst. 33 Low-molar-mass PGA samples display lower crystallinity, relatively poor thermal and mechanical behavior, and higher water permeability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lu et al reported the synthesis of high-molar-mass PGAs (20–250 kg·mol –1 ) in bulk at 130–150 °C using diphenyl bismuth bromide . Chen and co-workers studied the synthesis and catalytic activities of bis­(triazol) derivatives of Bi 3+ complexes with fluorinated and nonfluorinated ligands in the bulk ROP of G and attained high-molar-mass (52 kg·mol –1 ) PGA homopolymers . The melt ring-opening transesterification polymerization of PLAs has been studied using bismuth (III) subsalicylate (BiSS), an effective, relatively low-cost, and commercially available catalyst …”
Section: Introductionmentioning
confidence: 99%